2016
DOI: 10.7554/elife.15564
|View full text |Cite
|
Sign up to set email alerts
|

The target of the DEAH-box NTP triphosphatase Prp43 in Saccharomyces cerevisiae spliceosomes is the U2 snRNP-intron interaction

Abstract: The DEAH-box NTPase Prp43 and its cofactors Ntr1 and Ntr2 form the NTR complex and are required for disassembling intron-lariat spliceosomes (ILS) and defective earlier spliceosomes. However, the Prp43 binding site in the spliceosome and its target(s) are unknown. We show that Prp43 fused to Ntr1's G-patch motif (Prp43_Ntr1GP) is as efficient as the NTR in ILS disassembly, yielding identical dissociation products and recognizing its natural ILS target even in the absence of Ntr1’s C-terminal-domain (CTD) and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 48 publications
(79 reference statements)
8
78
1
Order By: Relevance
“…For the first three nucleotides at the 5’ end (U1–U3) two alternative conformations are observed (Figure 1—figure supplement 2). The structure reveals the basis for the sequence-independent RNA binding of Prp43 which is in line with previous biochemical data (Fourmann et al, 2016b; Bohnsack et al, 2009; Tanaka and Schwer, 2006). …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For the first three nucleotides at the 5’ end (U1–U3) two alternative conformations are observed (Figure 1—figure supplement 2). The structure reveals the basis for the sequence-independent RNA binding of Prp43 which is in line with previous biochemical data (Fourmann et al, 2016b; Bohnsack et al, 2009; Tanaka and Schwer, 2006). …”
Section: Resultssupporting
confidence: 90%
“…To dismantle purified ILSs (Fourmann et al, 2016b), samples were incubated with distinct combinations of a 10-fold molar excess over the spliceosome of recombinant scPrp43, ctPrp43, ctPrp43-IDSB, ctPrp43-HT, ctPrp43-HL, ctPrp43-HT&HL and scNtr(1•2). An additional step of incubation was performed for the variant ctPrp43-IDSB in the presence of 0.5 mM DTT for 5 min at 23°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that the spliceosomal target of Prp43 is the pre-mRNA branchsite/U2 snRNP interaction (42). Our data revealed that Prp43 fused to the GP motif of Ntr1 is a minimal discard enzyme leading to spliceosome disassembly, while Ntr2 is not strictly required for disassembly (42).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ntr2 is not essential for association of Prp43 with the spliceosome, yet its presence is required to prevent Prp43-mediated disruption of intact spliceosomal intermediates other than the intron-lariat spliceosome. 118 Thus, after accommodation of Prp43, Brr2 might further modulate Prp43 activities based on its intractions with Ntr2. Similar to the structure of a post-step 1 spliceosome lacking Prp16, 103 Brr2 is also flexibly tethered in a post-catalytic intron-lariat spliceosome and Prp43 has not been located in that structure, 81 presently leaving the structural basis for such putative regulatory interactions unresolved.…”
Section: Brr2 Regulation During Splicingmentioning
confidence: 99%